Cidadania e educação ambiental na interpretação do docente de educação fundamental do município DE Maceió, Alagoas. - Ayres, Fernando Guilherme Silva (2007)
In the present work we develop a qualitative research involving 28 teachers, of several disciplines and 4 supervisors, respectively belonging to 4 public schools of Maceió City (AL). The objective of our research consists of analyzing the educative activities perceived by the teachers of Basic Public Education with respect to Environmental Education. We intend to identify and to characterize the interpretations given by them on central concepts appearing in the discussion of the theme such as Environment, Citizenship, Ecological Citizenship or Ecocitizenship and Environmental Education. As a result of our research we observe in these schools a severe lack of interdisciplinary approach and a lack of supervision, including those starting from the official institutions, meanly CREAMB in Maceio City, which are, surprisingly, completely unknown. This is one of the chief reasons by which the habitual practice of environmental education is completely naïve. Consequently, this habitual practice is centered on merely spontaneous insights of insufficiently prepared teachers, which are not accompanied of on firm theoretical basis. In this context the naïve conservationism approach is emphasized instead of a critical discussion involving the complex interrelationships between Nature and Society. The habitual approach of environmental education is reductionist, naïve, and centered merely upon environment conservation, which is an insufficient approach in order to offer a good conception on Eco-citizenship. One important result of our thesis consists of appointing the necessity of providing a critical approach of environmental education theoretically founded on seminal thinkers of all the cultures.